Indications and Complications Associated with the Removal of 506 Pieces of Vaginal Mesh Used in Pelvic Floor Reconstruction: A Multicenter Study - John R. Miklos (2018)
STUDY OBJECTIVE: Synthetic mesh utilized to treat stress urinary incontinence (SUI) and pelvic organ prolapse (POP) can often result in postoperative complications. The objectives of this study were to determine: 1) the most common indications for mesh removal; 2) the incidences of the removal of specific mesh procedures (such as suburethral sling [SUS], transvaginal mesh [TVM], or sacrocolpopexy); and 3) the idences and types of surgical complications associated with mesh removal.DESIGN: This was a retrospective study. Design Classification: Canadian Task Force II-3.SETTING: Three tertiary referral centers in the United States.PATIENTS: We examined data from all patients at the three centers who underwent surgical removal of synthetic materials from previous SUS, TVM, and sacrocolpopexy procedures for mesh-related complications from 2011 to 2013.INTERVENTION: Patients underwent vaginal, intra-abdominal, and inguinal mesh revisions by cutting, partial removal, or total removal of the mesh for mesh-related complications.MEASUREMENTS AND RESULTS: Overall, 445 patients with complications underwent mesh removal laparoscopically, via groin dissection and/or transvaginally. There were a total of 506 mesh products removed. Of these, 56.5% were slings and 43.5% were for pelvic organ prolapse (POP). Synthetic mesh removed from patients included: transvaginal mesh (TVM) anterior for anterior vaginal prolapse, TVM posterior for posterior vaginal prolapse, sacrocolpopexy mesh, and suburethral slings (SUS) for stress urinary incontinence. Synthetic SUS removed included: retropubic (RPS), transobturator (TOT), and single-incision slings (SIS). TOT was the most common type of sling removed. Patients with a sling who only complained of vaginal pain with or without intercourse underwent a vaginal approach for surgical revision/removal of the sling (86.6%). Patients with an RPS with lower abdominal/suprapubic pain and vaginal pain underwent a vaginal and laparoscopic approach for sling removal (18.4%). Patients with a TOT sling who complained of vaginal and groin pain underwent a vaginal and inguinal approach for sling removal (4.3%). In patients who had POP mesh removal, 42.3% had an anterior TVM, 30.6% had a posterior TVM, 14% had both anterior and posterior TVMs, and 13.1% underwent sacrocolpopexy mesh removal. Complications encountered during mesh revision/removal surgery were: two blood transfusions from complete RPS removal (vaginal and laparoscopic approach), three urethral injuries during TOT sling removal (vaginal approach), two ureteral injuries during anterior vaginal wall mesh removal, and two rectal injuries during posterior vaginal wall mesh removal. All injuries were repaired at the time of mesh removal without recurrence.CONCLUSION: In our study, the most common indication for mesh removal was pain with or without intercourse. The most common mesh procedure resulting in removal was the TOT sling. Use of a vaginal approach only for sling removal had the lowest incidence of intraoperative complications. Laparoscopic RPS removal had the highest incidence of required blood transfusions, anterior TVM had the highest incidence of ureteral injury, and posterior TVM had the highest incidence of rectal injury. Overall, sling, TVM, and sacrocolpopexy mesh removal are safe procedures when performed by experienced surgeons.